The proportion and risk factors of fatal outcomes among severely and critically ill COVID-19 patients: A hospital experience, Baghdad, Iraq 2021 - Saleem, Ibrahim A. (Journal of the Faculty of Medicine Baghdad, 2022)
Background: Severe forms of Coronavirus disease 2019 (COVID‐19) were found among 6 - 10% of all COVID-19 patients. Acute respiratory distress syndrome ARDS is non-cardiogenic pulmonary edema manifested by the rapid development of shortness of breath, tachypnea, and hypoxemia. Patients’ outcomes after critical care for COVID-19 have not been adequately documented in this low-resource environment, despite advocacy for prevention and response measures in low- and middle-income countries.Objectives: To highlight the rate of severe illness among COVID-19 patients and its associated factors in Al-Imam Ali Hospital, Baghdad-Iraq 2021.Patients and Methods: A descriptive cross-sectional study on cases with severe and critical COVID-19 illness (with ARDS) admitted to the isolation ward in Al-Imam Ali Hospital from 23 March to 23 May, 2021. All COVID-19 patients admitted in a severe or critical state were included. A data collection form was filled by the researcher. The P value of < 0.05 was used to determine statistical significance. Ethical Approval was obtained.Results: A total of 504 severely ill COVID-19 patients were included in this study. There were 71 (14.1%) patients below 45 years of age. Males formed 40.9% of patients while that of females was 59.1%. Fever was the presenting symptom in 381 (75.6%) patients, 197 (39.1%) patients had anosmia, and 192 (38.1%) had ageusia. There were 358 (71.0%) survivors while 146 (29.0%) died. Patients aged 65 years or more had more possible risk for death than those below 65 years (OR=1.14, 95% CI =0.6-2.2). Female gender appeared to be protective compared to male gender (OR=0.52, 95% CI =0.35-0.77). Ex-smokers had a higher risk than non-smoker and current smokers (OR for ex-smoker=4.38, 95% CI 2.6-7.5), and (OR for current smoker=1.7, 95% CI 0.98-3). Renal disease was found to be a risk factor leading to death (OR=2.9; 95% CI=1.73-5.1). Diabetes Mellitus, respiratory diseases, and solid cancer showed a high risk for death, [OR=2.3, 95% CI=1.4-4; OR=1.7; 95% CI=1.1-2.9, OR=8, 95% CI=3.3-19 respectively]. Patients with three comorbidities had a higher mortality risk, OR=1.6, 95% CI=1.3-2.Conclusion: This study concluded that mortality of severely and critically ill COVID-19 patients was 29%, and males and older patients were risk factors for death. In addition to; ex-smoker, alcoholic, and patients with baseline comorbidities appeared to be risk factors for mortality. Finally; laboratory tests and Pao2/Fio2 ratio can be used to predict the outcome.